2003
DOI: 10.1105/tpc.012955
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsisppi1Mutant Is Specifically Defective in the Expression, Chloroplast Import, and Accumulation of Photosynthetic Proteins[W]

Abstract: The import of nucleus-encoded proteins into chloroplasts is mediated by translocon complexes in the envelope membranes. A component of the translocon in the outer envelope membrane, Toc34, is encoded in Arabidopsis by two homologous genes, atTOC33 and atTOC34 . Whereas atTOC34 displays relatively uniform expression throughout development, atTOC33 is strongly upregulated in rapidly growing, photosynthetic tissues. To understand the reason for the existence of these two related genes, we characterized the atTOC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
216
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(234 citation statements)
references
References 43 publications
18
216
0
Order By: Relevance
“…Of these genes, 1998 (8.2%) were significantly upregulated in the wild type and 2268 (9.3%) in ppi2 ( Figure 3A; see Supplemental Data Set 4 online). Our transcriptomics data confirmed the trend that photosynthetic proteins are expressed at lower levels in the import mutant as previously reported in published microarray, SAGE and RT-PCR data (Kubis et al, 2003;Kakizaki et al, 2009;Lee et al, 2009b). Notably, 84% of the downregulated genes reported in the SAGE data set were also found downregulated under our experimental conditions (see Supplemental Data Set 4 online).…”
Section: Proteins For Photosynthetic Functions Are Downregulated At Tsupporting
confidence: 76%
See 1 more Smart Citation
“…Of these genes, 1998 (8.2%) were significantly upregulated in the wild type and 2268 (9.3%) in ppi2 ( Figure 3A; see Supplemental Data Set 4 online). Our transcriptomics data confirmed the trend that photosynthetic proteins are expressed at lower levels in the import mutant as previously reported in published microarray, SAGE and RT-PCR data (Kubis et al, 2003;Kakizaki et al, 2009;Lee et al, 2009b). Notably, 84% of the downregulated genes reported in the SAGE data set were also found downregulated under our experimental conditions (see Supplemental Data Set 4 online).…”
Section: Proteins For Photosynthetic Functions Are Downregulated At Tsupporting
confidence: 76%
“…The receptors are required for photosynthetic growth because their loss-of-function produces plants with a pale green or albino phenotype (Jarvis et al, 1998;Bauer et al, 2000). The analysis of Toc33 mutants (ppi1 for plastid protein import 1) suggested that this receptor may be preferentially involved in the import of photosynthetic proteins (Kubis et al, 2003). Similarly, the loss of Toc159 function (ppi2) results in albino plants that do not grow beyond the cotyledon stage on soil because the accumulation of photosynthetic proteins is significantly reduced (Bauer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The import efficiency of four photosynthesis-related proteins (RbcS, chlorophyll a/b-binding protein [Cab], and PORA and PORB [protochlorophyllide oxidoreductases A and B]) into ppi1 mutant chloroplasts is reduced compared to wild-type chloroplasts (Jarvis et al, 1998). Furthermore, the steady-state amount of RbcS has approximately 50% reduction in ppi1 chloroplasts (Kubis et al, 2003), revealing that deficiency of Toc33 Figure 7. Up-regulation of translocon and ribosomal genes by CIA2.…”
Section: Discussionmentioning
confidence: 99%
“…Two differentially expressed genes of the Toc34 family are present in Arabidopsis, atTOC33, and atTOC34 (Jarvis et al, 1998;Gutensohn et al, 2000), prompting the proposal that the proteins play specific roles during plastid development. atToc33 and atToc34 seem to exhibit some preferences for binding to transit peptides (Gutensohn et al, 2000;Jelic et al, 2003;Kubis et al, 2003), suggesting that they might be involved in the import of distinct preproteins. However, ectopic expression of atToc34 can rescue the pale phenotype of an atToc33 null mutant (Jarvis et al, 1998), ppi1, indicating that the GTPases play overlapping roles in plastid protein import.…”
Section: Introductionmentioning
confidence: 99%